Local Wisdom Values in the Pujawali Tradition - Joni Pranata; Hadion Wijoyo; Agung Suharyanto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the local wisdom of the Buddhist community in Lombok, especially North Lombok in relation to the environment, nature, and plural social relations. The research method was carried out qualitatively on Buddhist communities in North Lombok Regency. This research results in the finding that basically the local wisdom of the Buddhist community is extracted from the experience of the community from the acculturation of the Majapahit Kingdom tradition which is very familiar with its environment and has long lived in a community culture that is one with nature, known asPujawali / memareq / worship. The local wisdom of Pujawali custom is a social and cultural condition which contains cultural values that respect and are adaptive to the natural surroundings, and are arranged steadily in a society's customs. Even though they are often considered old-fashioned, the values they teach and the practices they carry out are still a regular way of maintaining the environment and good relations between and within religious communities because they still hold strong beliefs about protecting nature means protecting life. Mujawali's wisdom teaches about maintaining harmony and unity, things that cannot be negotiated because actually the people of North Lombok have one ancestor in line with that in North Lombok the people hold the principle of helping merenten (we are all brothers).